2006
DOI: 10.1128/iai.02000-05
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Bhmp39 Major Outer Membrane Proteins of Brachyspira hyodysenteriae

Abstract: The enteric, anaerobic spirochete Brachyspira hyodysenteriae is the causative agent of swine dysentery, a severe mucohemorrhagic diarrheal disease of pigs that has economic significance in every major porkproducing country. Recent investigation into potential vaccine candidates has focused on the outer membrane proteins of B. hyodysenteriae. Bhmp39 (formerly Vsp39) is the most abundant surface-exposed outer membrane protein of B. hyodysenteriae; its predicted gene sequence has previously been shown to share se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Of the bhmp39a-h , forming a set of paralogous genes, bhmp39f was present in almost all isolates, while bhmp39h could not be detected at all. This is in contrast to former studies that demonstrated a wide distribution of both genes [ 43 ]. The remaining OMPs encoding genes ( bhlp16 and bhlp17 .…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Of the bhmp39a-h , forming a set of paralogous genes, bhmp39f was present in almost all isolates, while bhmp39h could not be detected at all. This is in contrast to former studies that demonstrated a wide distribution of both genes [ 43 ]. The remaining OMPs encoding genes ( bhlp16 and bhlp17 .…”
Section: Discussioncontrasting
confidence: 98%
“…A reasonable explanation implicates that bhmp39f is not essential for the viability of the pathogen as it has recently been concluded for some plasmid genes possibly associated with virulence [ 41 ]. It should also be emphasized, that any negative finding could be the result of a false negative PCR due to variations in primer binding sites, which may particularly be the case in OMP genes that are involved in antigenic variability [ 43 ]. Whether mismatches result in an altered functionality of the protein cannot be determined at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated from T. pallidum ssp. pallidum (Nichols strain) as described elsewhere (Witchell et al, 2006). The orientation-specific RT-PCR sense and antisense primers for tp0750 and tp0751 (pallilysin) are indicated in Table 2.…”
Section: Rna Extraction and Rt-pcrmentioning
confidence: 99%
“…An alternative approach may be to generate subunit vaccines that might be delivered by the expression of recombinant B. hyodysenteriae proteins on a bacterial delivery vector [113]. Investigations into potential targets for such recombinant vaccines have focused on outer membrane proteins [114,115,116,117], flagelar proteins [118,119] or iron storage proteins [120], although in most occasions recombinant vaccines tested have failed to provide enough protection in pigs.…”
Section: The Fight Against Sdmentioning
confidence: 99%